2021
DOI: 10.1038/s43247-021-00253-0
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic phytoplankton are a potentially important source of benzenoids to the remote marine atmosphere

Abstract: Benzene, toluene, ethylbenzene and xylenes can contribute to hydroxyl reactivity and secondary aerosol formation in the atmosphere. These aromatic hydrocarbons are typically classified as anthropogenic air pollutants, but there is growing evidence of biogenic sources, such as emissions from plants and phytoplankton. Here we use a series of shipborne measurements of the remote marine atmosphere, seawater mesocosm incubation experiments and phytoplankton laboratory cultures to investigate potential marine biogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…A recent study from Rocco et al. (2021) also reported that some VOCs previously thought to be anthropogenic, that is, benzenoids, can be instead emitted by oceanic phytoplankton.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…A recent study from Rocco et al. (2021) also reported that some VOCs previously thought to be anthropogenic, that is, benzenoids, can be instead emitted by oceanic phytoplankton.…”
Section: Resultsmentioning
confidence: 94%
“…The Omaruru River delta aquifer, approximately 100 km inland (east) of Henties Bay, receives less than 50 mm/year of precipitation, and acts as a barrier for the river which does not flow at Henties Bay (Geyh and Plothner, 1995). A recent study from Rocco et al (2021) also reported that some VOCs previously thought to be anthropogenic, that is, benzenoids, can be instead emitted by oceanic phytoplankton.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, Rocco et al (29) suggested a phytoplankton source of benzene and toluene in the surface ocean. They used mesocosm and phytoplankton culture experiments to show that phytoplankton species produce benzene and toluene at variable rates.…”
Section: Introductionmentioning
confidence: 99%